Pengaruh Konsentrasi NaOH pada Proses Deasetilasi Kitin terhadap Derajat Deasetilasi Kitosan - Aldila, Herman; Nuryadin, Atin; Dalimunthe, Desy Yuliana (Jurnal Riset Fisika Indonesia, 2021)
Chitosan have been successfully produced from the dried shrimp home industry waste (Bangka, Indonesia). Extraction of chitosan was carried out in four steps: deproteinization, demineralization, decolorization and deacetylation of chitin. The effect of NaOH concentration on deacetylation process was studied. The results shown that the increase of NaOH concentration from 20% to 60%, the chitosan DD increased. The diffusion rate of OH- causes increment of OH- attack to the amino group thus realizing the effective deacetylation of chitin. The highest chitosan DD was up to 69.49% is achieved under the optimized conditions of this process and the occurrence of deacetylation structurally demonstrated by the Fourier transform infrared (FTIR) characterization.